A Context-oriented Communication Algorithm for Advance Care Planning: A Model to Assist Palliative Care in Heart Failure. Issue 5 (September 2018) - Kim, JinShil; Kim, Shinmi; Shin, Mi-Seung; Jin, Jae Ok; Kim, Yunmi; Lee, Mee-Ok
Abstract : Background: Access to consultation or referral for decisions about advance care planning (ACP) is limited, particularly for nonmalignant models pertinent to palliative care in heart failure (HF). Objectives: The aim of this study was to solicit professional opinions about the feasibility of using an exemplary context-oriented communication algorithm for ACP discussions. Methods: Using a panel of expert physicians and nurses in cardiovascular care, a 3-round Delphi study was conducted to evaluate the proposed model. Results: A consensus was determined based on a content validity ratio (CVR) of 0.318 or greater, a critical value for selection of an item scored as important (≥4 on a 5-point Likert scale). A total of 50, 44, and 38 experts in Korea completed each round, respectively. Item evaluation did not differ across rounds (Friedman χ 2 > P = .05), except for timing of the ACP discussion. A lack of consensus was observed on the issue of after HF diagnosis for right timing of the ACP discussion across rounds (CVRs from −0.80 to −0.83); consensus was reached on the expectation of a terminal state (CVRs from 0.60 to 0.78). Content validity ratios were moderately high for Korean advance directive, ranging from 0.59 to 0.91. Experts also reached consensus about each of 5 steps of a communication model—patients' determination of decisional capacity (CVR, 0.72–1.0), awareness (CVR, 0.95–1.0), willingness for advance care planning (CVR, 0.76–0.84), family dynamics (CVR, 0.92–1.0) and patient readiness for advance care planning (CVR, 0.76–0.95). Conclusions: A context-oriented communication model could be used to facilitate the decision-making process for palliative care and continuity of care in HF. Abstract : Supplemental digital content is available in the text.